Sufficient and Necessary Conditions for Information to have Social Value in Pure Exchange - HAKANSSON, NILS H.; KUNKEL, J. GREGORY; OHLSON, JAMES A. (Journal of Finance, 1982)
ABSTRACT This paper extends, corrects, and unifies earlier statements concerning the social value of public information as well as the no‐trading conditions in pure exchange. Sufficient and necessary conditions are provided for both the single‐period and two‐period cases in a postsignal trading model. The social value of information is shown to be closely linked to the allocational efficiency of the market, the degree of homogeneity of prior beliefs, and of information structures, the time‐additivity of preferences, and the efficiency of endowments. We conclude that the case in favor of public information is much stronger than previously suggested.